(untitled) (Agroindustria, Sociedad y Ambiente, 2022)
The strong dependence of nations on fossil fuels, particularly oil, is a major concern for energy security since it plays a vital role in generating economic and social advances in developing countries. Reason why, through an exhaustive documentary review, the energy situation for future generations is addressed, framed in a post-oil era where alternative energies, such as solar photovoltaic, wind and biofuels, due to the significant boom that have in recent years have an energy responsibility to meet the required demand. Likewise, biogas is analyzed as an alternative fuel as a result of a series of advantages it has, determining that state policies must be generated that involve governments, companies and communities in the implementation and development of this biofuel.